Bacteriophage Cocktails Protect Dairy Cows Against Mastitis Caused By Drug Resistant Escherichia coli Infection - Guo, Mengting; Gao, Ya; Xue, Yibing; Liu, Yuanping; Zeng, Xiaoyan; Cheng, Yuqiang; Ma, Jingjiao; Wang, Hengan; Sun, Jianhe; Wang, Zhaofei; Yan, Yaxian (Frontiers in Cellular and Infection Microbiology, 2021)
Mastitis caused by Escherichia coli (E. coli) remains a threat to dairy animals and impacts animal welfare and causes great economic loss. Furthermore, antibiotic resistance and the lagged development of novel antibacterial drugs greatly challenge the livestock industry. Phage therapy has regained attention. In this study, three lytic phages, termed vB_EcoM_SYGD1 (SYGD1), vB_EcoP_SYGE1 (SYGE1), and vB_EcoM_SYGMH1 (SYGMH1), were isolated from sewage of dairy farm. The three phages showed a broad host range and high bacteriolytic efficiency against E. coli from different sources. Genome sequence and transmission electron microscope analysis revealed that SYGD1 and SYGMH1 belong to the Myoviridae, and SYGE1 belong to the Autographiviridae of the order Caudovirales. All three phages remained stable under a wide range of temperatures or pH and were almost unaffected in chloroform. Specially, a mastitis infected cow model, which challenged by a drug resistant E. coli, was used to evaluate the efficacy of phages. The results showed that the cocktails consists of three phages significantly reduced the number of bacteria, somatic cells, and inflammatory factors, alleviated the symptoms of mastitis in cattle, and achieved the same effect as antibiotic treatment. Overall, our study demonstrated that phage cocktail may be a promising alternative therapy against mastitis caused by drug resistant E. coli.